Salivary Cortisol Fluctuations and Hyperglicemic Stress in Patients with Abdominal Obesity - Corina Dima-Cozma; Andreea Szalontay; Cristina Ghiciuc; Sebastian Cozma; Francesca Romana Patacchioli (Romanian Society of Oral Rehabilitation, 2012)
Objectives We investigated a possible relationship between the onset of hyperglycaemia in prediabetes and the perturbations of hypothalamo-pituitary-adrenocortical axis. Material and methods The study included 20 patients, younger than 65 years (52.15 ± 4.55), having risk factors for diabetes mellitus like abdominal obesity or positive family history. All patients underwent oral glucose tolerance test (OGTT) and 4 concomitant determinations of salivary cortisol levels, in basal condition, at wakening, and at 1, 2, and respectively 3 hours after oral administration of 75 grams of glucose. Results The evolution of salivary cortisol levels in the morning showed that, concomitant with the peak of hyperglycaemia at the third moment of determination (221.75 ± 39.3 mg/dl) it was registered a mild tendency of increasing of salivary cortisol, at the same time (5.26 ± 2.76 mg/ml). Conclusion The simple method of salivary cortisol measurement could become a useful tool for the HPA axis functionality screening.